Comparative Study of Students' Perceived Stress Scale Score after 2 Years Period of Studying Pharmacy in IIUM - Soe, May Khin Soe; Abdul Rahman, Mohammad Nasrin (2015)
University students are exposed to academic stress due to exams, co-curricular activities, quizzes, presentations and discussions. This study compares the students’ perceived stress scale after 2 years period of studying Bachelor of Pharmacy in International Islamic University Malaysia (IIUM). The data of this study (year 2014) was compared with the data of the same previous study done in the year 2012. A set of questionnaires were given to all final year pharmacy students. They were given the same perceived stress scales questionnaire adapted from Cohen, Kamarck, and Mermelstein (1983), in the year 2012 (during their second year of study), and in the year 2014 (during their fourth year of study). It was found that the mean value of PSS score for male in 2014 is 30.13± 6.62, compared to 24.26 ± 6.53 in the year 2012. Paired sampled T-test p=0.000 (p < 0.05). There is significant different of the mean data for both years. For female, The 2014 PSS score is 31.26 ± 3.20, compared to 27.44 ± 5.19 in the year 2012. Paired sample T-test p= 0.136 (p>0.05). There is no significance difference of the mean data for both years. The PSS score for overall male and female in 2014 is 30.80 ± 4.89, compared to 2012 which is 26.17± 5.94. Paired Sampled T-test p = 0.000 (p<0.05). There is significance difference of the mean data for both years. The results of this research alarms that students’ stress (PSS score) were significantly increased in final year because of heavy workload in both Academic and co-curricular activities. Thus, this study highlighted the early awareness in prevention of negative consequences among Educators and Pharmacy students. Take Home Message: Solutions were also recommended to improve the systems so that the stress level among students can be manageable in the future. Keywords: Perceived Stress Scales (PSS score), Academic Stress, Pharmacy Students, Pharmacy Education